DISPLAYING SOCIAL MEDIA ADS DI PKBM SAHABAT CENDIKIA - Handoko, Koko; Simanjuntak, Pastima; Elisa, Erlin; Zetli, Sri (ASOSIASI IDEBAHASA KEPRI, 2025)
The purpose of this Community Service is to see how PKBM Sahabat Cendikia uses social media advertising to increase the visibility of the institution and increase community participation in non-formal education programs. In today's internet era, using social media is one of the effective ways to reach a larger audience, especially the younger generation who are active on websites such as Facebook and Instagram. This service uses a qualitative descriptive approach and data collection through documentation, interviews, and observations. The service shows that displaying social media ads increases the number of students and improves the reputation of the institution in the community. Visual ad design, frequency of display, and audience segmentation are important components that determine the effectiveness of a digital campaign. These findings are expected to be a reference for other non-formal educational institutions to use social media wisely to promote themselves.